2023
DOI: 10.1021/acs.joc.2c02776
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed β-Acylalkylation of Allylbenzene Derivatives with Allyl Alcohols via C–C Bond Cleavage

Abstract: We report here a deallylative β-acylalkylation reaction of allylbenzene derivatives with allyl alcohols in the presence of Cp*Rh catalysts. Allylbenzenes possessing pyridyl and pyrazolyl directing groups were converted to β-aryl ketones via the cleavage of C(aryl)−C(allyl) bonds. Synthesis of a quinoline derivative from a β-aryl ketone product bearing a pyrazolyl group was also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In recent years, several elegant examples have been reported that addressed these issues to some extent. For example, chelation-assisted functionalizations of allylbenzenes have been achieved via the activation of nonpolar C–C bonds . Our group achieved a Ag-catalyzed 1,4-aryl migration of γ,γ-disubstituted triflic amides from carbon to the nitrogen center, which cleaved the C–C bond far from the polar group through a radical pathway .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several elegant examples have been reported that addressed these issues to some extent. For example, chelation-assisted functionalizations of allylbenzenes have been achieved via the activation of nonpolar C–C bonds . Our group achieved a Ag-catalyzed 1,4-aryl migration of γ,γ-disubstituted triflic amides from carbon to the nitrogen center, which cleaved the C–C bond far from the polar group through a radical pathway .…”
Section: Discussionmentioning
confidence: 99%